2023
DOI: 10.1002/hbm.26262
|View full text |Cite
|
Sign up to set email alerts
|

The widespread action observation/execution matching system for facial expression processing

Abstract: Observing and understanding others' emotional facial expressions, possibly through motor synchronization, plays a primary role in face‐to‐face communication. To understand the underlying neural mechanisms, previous functional magnetic resonance imaging (fMRI) studies investigated brain regions that are involved in both the observation/execution of emotional facial expressions and found that the neocortical motor regions constituting the action observation/execution matching system or mirror neuron system were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 122 publications
0
1
0
Order By: Relevance
“…One possible explanation of this might be that angry facial expressions impair the PFC by the activation of limbic regions as self-regulation capacities are limited in concordance with the self-regulation model of Heatherton and Wagner [ 17 ]. In line, a current fMRI study in healthy participants delivered evidence that angry facial stimuli activate a widespread neural observation/execution network including the amygdala besides frontal areas including the precentral gyrus, right pallidum, several regions in the cerebellum, and brainstem [ 28 ]. Another general population study using angry versus happy faces as the stop signal in the SST indicated that angry faces impair inhibitory control as they capture more attention compared to happy faces [ 29 ].…”
Section: Introductionmentioning
confidence: 82%
“…One possible explanation of this might be that angry facial expressions impair the PFC by the activation of limbic regions as self-regulation capacities are limited in concordance with the self-regulation model of Heatherton and Wagner [ 17 ]. In line, a current fMRI study in healthy participants delivered evidence that angry facial stimuli activate a widespread neural observation/execution network including the amygdala besides frontal areas including the precentral gyrus, right pallidum, several regions in the cerebellum, and brainstem [ 28 ]. Another general population study using angry versus happy faces as the stop signal in the SST indicated that angry faces impair inhibitory control as they capture more attention compared to happy faces [ 29 ].…”
Section: Introductionmentioning
confidence: 82%
“…The ability to recognize emotional expressions is critical for survival and plays a pivotal role in successful social interactions. Converging evidence has suggested that the processing of emotional faces triggers the activation of widespread brain regions (for a review, see [ 1 ]), including motor areas such as the supplementary motor, premotor, and primary motor cortex [ 2 , 3 ]. The activation of the motor system during the perception of emotional faces has been interpreted as reflecting mechanisms of the preparation of adaptive motor responses, such as the fight/flight response [ 4 , 5 ], consistently with the long-held view that emotions prime the human body for action [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%